Optimalisasi Produksi Kuliner Berbahan Dasar Mangrove Dalam Meningkatkan Daya Saing Usaha Di Kabupaten Muara Gembong - Budi Satria; Timorora Sandha Perdhana (Jurnal Kajian Ilmiah, 2023)
This research aims to; find out whether there is a significant positive effect between raw material inventory control on the production process, find out whether there is a significant positive effect between production process planning on the production process, find out whether there is a significant positive effect between raw material inventory control on business competitiveness, find out whether there is an influence significant positive relationship between production process planning and business competitiveness and to determine whether there is a significant positive effect between the production process and business competitiveness. The research method used in this study was a survey method using descriptive research methods with a quantitative approach involving 32 business actors in the Mangrove-Based culinary field in Muara Gembong Regency. The results of the study show that Raw Material Inventory Control has a significant effect on Business Competitiveness. In direct and indirect testing it is known that Raw Material Inventory Control has a direct and significant effect on the Competitiveness of Mangrove-Based Culinary Businesses in Muara Gembong Regency. While the Production Planning Process has a significant effect on Business Competitiveness. This means that the better the Production Planning Process will be able to improve the competitive positioning of Mangrove-Based culinary businesses in Muara Gembong Regency.